Potrčevo videnje svobode leta 1945 - Debeljak, Renata (Studia Historica Slovenica, 2016)
This piece shows the view of the war and of the coming freedom from the Slovenian writer, playwright and publicist Ivan Potrč (1913-1993); that spent the final year of the war as a font line correspondent for Borba and Ljudska pravica. In his reportages and ideologically affirmed short war prose of that time he has in a short memoir-autobiographical discourse themed his suffering in Mauthausen, repeatedly stressed the victorious struggle of partisans against the occupying forces, advocated for a socialist revolution and the conviction of domestic traitors, which is especially reflected in the mostly optimistically rounded texts in which he wove also his vision of the coming freedom. For him the path to freedom was intertwined with resistance, struggle and casualties, with the common desire for a free future. It was built with suffering, unity, loyalty, courage - in short socialist values, that he advocated even as a pre-war "communist". UDC
Keywords: druga svetovna vojna; literarni motivi; NOB; Potrč, Ivan; Slovenija; slovenska književnost; svetovna vojna 1939-1945; svoboda